2001
DOI: 10.2165/00129784-200101010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Medical Management of Chronic Heart Failure in Children

Abstract: Chronic heart failure (CHF) in children occurs mostly as a result of systolic dysfunction of the systemic ventricle or of congenital defects leading to large left-to-right shunts and pulmonary overcirculation. The ensuing symptoms and signs are similar in both cases, and include respiratory distress, poor feeding and growth, and hepatic congestion. Grading the severity of the symptoms accurately and reproducibly is important for studying CHF and the response to therapy. The Ross classification for young childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…[143][144][145] Delayed growth with retarded bone age is commonly observed in pediatric heart transplantation candidates. 146,147 Pediatric transplant recipients have generally exhibited normal growth rates after transplantation, but their absolute heights and weights tend to be in the lower range of normal.…”
Section: Canter Et Almentioning
confidence: 99%
“…[143][144][145] Delayed growth with retarded bone age is commonly observed in pediatric heart transplantation candidates. 146,147 Pediatric transplant recipients have generally exhibited normal growth rates after transplantation, but their absolute heights and weights tend to be in the lower range of normal.…”
Section: Canter Et Almentioning
confidence: 99%
“…Over the last 2 decades, however, digoxin has lost favor with many pediatric cardiologists, with only 28% of patients in the National Pediatric Cardiology Quality Improvement Collaborative (NPC‐QIC) discharged home on the medicine . Reasons for the decreased use of digoxin include question about its mechanism of action, concerns about toxicity, and availability of other pharmacological options . However, it has recently been suggested that digoxin might play a role in reducing interstage mortality …”
Section: Introductionmentioning
confidence: 99%
“…14 Reasons for the decreased use of digoxin include question about its mechanism of action, concerns about toxicity, and availability of other pharmacological options. 15 However, it has recently been suggested that digoxin might play a role in reducing interstage mortality. 16 The objective of our study was to evaluate the association of outpatient digoxin use with interstage mortality in infants with single ventricle congenital heart disease in a multicenter study using data from the Pediatric Heart Network Single Ventricle Reconstruction (SVR) trial.…”
mentioning
confidence: 99%
“…16 Tube feeding is often necessary to provide adequate energy for growth. The Ross classification of HF uses growth and responses to feeding as criteria to describe degree of HF 12 (Table 1).…”
Section: Incidence Of Congenital Heart Disease and Cardiomyopathy In mentioning
confidence: 99%